Effet des pratiques enseignantes sur les manières d'étudier en première année universitaire : une approche comparative entre différentes composantes - Amélie Duguet
This article is a continuation of work on the construction of ways of studying young people entering university. It envisages the role of a factor hitherto little discussed, that of teaching practices, through the way they are perceived by students. Making a comparison between the components of Humanities and Social Sciences and Law, we show in support of an empirical survey of 677 first year if individuals collecting lecture practices helps explain the ways of studying individuals in law, it has however no effect on those of Humanities and Social Sciences students.